2021
DOI: 10.3390/cells10082031
|View full text |Cite
|
Sign up to set email alerts
|

Inborn Errors in the LRR Domain of Nod2 and Their Potential Consequences on the Function of the Receptor

Abstract: The innate immune system plays a critical role in the early detection of pathogens, primarily by relying on pattern-recognition receptor (PRR) signaling molecules. Nucleotide-binding oligomerization domain 2 (NOD2) is a cytoplasmic receptor that recognizes invading molecules and danger signals inside the cells. Recent studies highlight the importance of NOD2′s function in maintaining the homeostasis of human body microbiota and innate immune responses, including induction of proinflammatory cytokines, regulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 104 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…Our data revealed that NOD2 was upregulated in the maternal lymph node during early pregnancy, and the NOD2 protein was located in the subcapsular sinus and lymph sinuses. NOD2 can recognize danger signals in the cells and plays an essential role in maintaining the innate immune response [ 40 ]. First trimester trophoblast cells express NOD2 that contribute to recognizing and responding to invasive intracellular pathogens [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data revealed that NOD2 was upregulated in the maternal lymph node during early pregnancy, and the NOD2 protein was located in the subcapsular sinus and lymph sinuses. NOD2 can recognize danger signals in the cells and plays an essential role in maintaining the innate immune response [ 40 ]. First trimester trophoblast cells express NOD2 that contribute to recognizing and responding to invasive intracellular pathogens [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, during infection with M.tb , the bacteria perturb the host metabolism by inducing a metabolic switch toward aerobic glycolysis in CD14+ monocytes or CD3+ T cells isolated from human peripheral blood mononuclear cells (PBMCs). The metabolic shift was dependent on TLR2 and was facilitated by the activation of the AKT-mTOR (mammalian target of rapamycin) pathway ( Lachmandas et al., 2016 ; Alipoor and Mirsaeidi, 2021 ). Regarding the presence and importance of EVs surface TLR ligands, it can be expected that these EVs could induce reprogramming of metabolic pathways in the recipient cells.…”
Section: The Mechanisms Of Evs In Modulation Of Immune Responses Duri...mentioning
confidence: 99%
“…PRR sensors recognize a broad pattern of PAMP antigens and play an essential role in developing innate and adaptative immune responses. The best-known PRR sensors that PAMP activates are classified in 4 families: (i) Toll-like receptors (TLR), (ii) retinoic acid-inducible gene I (RIG-I)-like receptors (RLRs) that includes RIG I, melanoma-associated differentiating protein 5 (MDSA5), and Laboratory of Genetics and Physiology 2 (LGP 2) (iii) NOD-like receptors family (NLR) (NOD- nucleotide-binding oligomerization domain), and (iv) C-type lectin sensors ( 7 , 8 ). After recognizing the danger signals, the cell activates the molecular effectors mediating the aggression response.…”
Section: Introductionmentioning
confidence: 99%